Caryophyllaeid infestations on the sex and size of Walking Catfish Clarias batrachus (Bangladesh Journal of Animal Science, 2012)
An investigation was carried out on the caryophyllaeid infestations in walking catfish Clarias batrachus in relation to different sexes and size groups during August 2010 to July 2011. A total of 227 host fish were collected from different water bodies of Mymensingh for examination. Among them 188 C.batrachus were infested with 1432 parasites by five different caryophyllaeid cestodes species. Prevalence was 100% during November and December both in male and female hosts. In other period of the year, female were more infested. In male fishes, the highest intensity and abundance were recorded in December and index of infection in February. In female fishes, the lowest infestations were recorded during the months of August, September and October. Parasites showed different levels of infestations in different size groups of fishes. Higher prevalence was recorded in medium size fishes in winter and summer and smaller size fishes in autumn. However, the index of infestations and abundance were higher in same size group only in winter season. The lowest prevalence and mean intensity were recorded in rainy season and abundance was in summer in smaller size group of fish.DOI: http://dx.doi.org/10.3329/bjas.v40i1-2.10792Bang. J. Anim. Sci. 2011. 40 (1-2): 56-59